Tren Penggunaan Uang Elektronik Terhadap Generasi Milenial - Erwin Wijaya; M. Rachman Mulyandi (Universitas Pendidikan Nasional, 2021)
Currently in industry 4.0, electronic transactions have become a trend for people in Indonesia.Electronic transactions are payment mechanisms used electronically. Electronic money is anelectronic transaction payment mechanism. In this research using data collection method isliterature review. The data in this reseacrch were analyzed by reducing data, presenting dataand drawing conclusions. This reseacrch focusese on thr use of electronic monay towardsmilennials.